EGFR mutation prevalence, real-world treatment patterns, and outcomes among patients with resected, early-stage, non-small cell lung cancer in Canada. (November 2022) - Sara Kuruvilla, M.; Liu, Geoffrey; Syed, Iqra; Gwadry-Sridhar, Femida; Sheffield, Brandon S.; Sachdeva, Robin; Pencz, Alec; Zhan, Luna; Hueniken, Katrina; Patel, Devalben; Balaratnam, Karmugi; Khan, Khaleeq; et al.
Highlights: Adjuvant osimertinib was recently approved for EGFR mutation-positive NSCLC. The baseline characteristics of this target patient population are of interest. In a Canadian population, 23% of tested patients were EGFR mutation positive. Half of EGFR +  patients experienced disease recurrence, typically at distant sites. Overall survival was generally poor regardless of the therapy received. Abstract: Objectives: The ADAURA trial demonstrated the benefit of adjuvant osimertinib among patients with resected, early-stage, epidermal growth factor receptor-mutated ( EGFRm ) non-small cell lung cancer (NSCLC). To understand the potential population impact, it is critical to deduce the prevalence, management, and outcomes of this patient population in the real-world setting before use of adjuvant osimertinib. Materials and Methods: Using PALEOS (Pan-cAnadian Lung cancEr Observational Study) data (2012–2019), a retrospective, multi-center, observational cohort study was conducted among patients with early-stage (IB–IIIA) resected NSCLC who had not received neoadjuvant therapy. Study outcomes included EGFRm prevalence, treatment patterns, recurrence outcomes, and overall and disease-free survival (OS/DFS). Results: Among patients undergoing reflexive EGFRm testing by a pathologist at time of diagnosis irrespective of disease stage (N = 535), 23 % were EGFRm- positive; 15.9 % had common mutations and 5.6 % had uncommon mutations. Within the EGFRm -positive cohort (N = 156), mean age at diagnosis was 68 years, 65 % of patients were female, and 35 % were of Asian descent. At diagnosis, 48 %, 31 %, and 21 % had stage IB, II, or IIIA disease, respectively; 46 % received adjuvant therapy after resection. Half of patients experienced disease recurrence, typically involving distant sites; central nervous system metastasis varied from 12 % to 15.0 % across disease stages. EGFR tyrosine kinase inhibitors were the most commonly received therapy after first metastatic recurrence. Median OS (DFS) was not reached, 71.2 (22.8) months, and 50.1 (18.0) months among stage IB, II, and IIIA patients. Patients with uncommon EGFRm had a lower probability of survival than those with common EGFRm (2 years: 87 % vs 91 %–94 %; 4 years: 56 % vs 73 %–82 %). Conclusion: Approximately-one-quarter of patients with resected, early-stage NSCLC were EGFRm -positive in this study. These patients had high recurrence rates and suboptimal long-term survival after treatment with current therapies. New adjuvant treatments are warranted.